ANALYSIS OF ENERGY-EFFICIENT OPERATING MODES AND PARAMETERS OF CASCADE PUMPING STATIONS - Shavazov, Abdulatif; Eshkuziyev, Khurshid; Ishanova , Dildora; Norboyev , Anvar (Innovatsion texnologiyalar, 2024)
The article provides an analysis of energy-efficient operating modes and parameters of cascade pumping stations. The operating mode of pump stations in irrigation systems is determined by a number of parameters, including structural design, technological, and electrical characteristics. In sugaring systems, it is believed that the operating order of existing pumping stations is determined by the parameters of one cathode. Including a structural device, technological and implemented in the form of electricity. For the “pump-motor-pressure pipe” system, the division of pumping units into pumps of different types is analyzed, taking into account the options for connecting pressure pipes, depending on the voltage value for the parameters of frequency converters, depending on the type of electric motors.